PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGIMPLEMENTASIKAN MODERASI BERAGAMA DI SMP NEGERI 6 LONG KALI - Muhammad Rohan Saputra; Sabran; Sri Susmiyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of Islamic Religious Education teachers in implementing religious moderation at SMP Negeri 06 Long Kali. This study uses a qualitative approach with a phenomenological research type. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used an interactive analysis model that includes data reduction, data presentation, and conclusion drawing, while data validity was tested through source and technique triangulation. The results show that Islamic Religious Education teachers have an important role in implementing religious moderation through four main roles: educators, guides, facilitators, and evaluators. As educators, teachers instill the values ​​of balance, tolerance, and mutual respect in the learning process. As guides, teachers provide direction and advice to students to maintain harmony and avoid conflict in social interactions. As facilitators, teachers create active learning through discussions and questions and answers so that students can understand various perspectives. Meanwhile, as evaluators, teachers assess not only cognitive aspects but also students' attitudes and behaviors in everyday life. Thus, the role of Islamic Religious Education teachers is crucial in fostering moderate religious understanding in students, even when available learning resources are relatively limited.